Analisis Kompetensi Profesional Guru dalam Menerapkan Pembelajaran Tematik di Sekolah Dasar - Romi Laspita; Indriyanto Indriyanto; Nasrul Nasrul (Indonesian Journal of Multidisciplinary on Social and Technology, 2024)
The professional competency of teachers referred to in this research is the education of teachers who teach in elementary schools (SD) in implementing thematic learning. At the elementary school level there are still teachers whose professional qualifications do not match the needs of elementary schools. If this can be done permanently, it cannot be denied that this will have an impact on teachers' professional competence in implementing thematic learning in the future. Thematic learning is a learning model that allows students to study academic concepts and principles comprehensively, meaningfully and authentically, individually and in groups. The type of research used in this research is a mixed/combination type of research or what is usually called mixed methods sequential explanatory model. This research aims to determine the professional competence of elementary school (SD) teachers in implementing thematic learning in elementary schools. From the results of interviews and observations made, it was proven that class Ib and IV teachers had prepared learning plans before the learning process began. Both teachers carry out the learning process based on themes that have been determined in the teacher's book and student's book. Both teachers carry out learning based on the learning implementation plan that has been prepared.